Xps structure analysis of tin/tic bilayers produced by pulsed vacuum arc discharge (2010)
TiN/TiC Bilayers were grown on 304 stainless steel substrates using physical vapour deposition assisted by pulsed arc plasma system (PAPVD) at two substrate temperatures (50º C and 150º C). X ray photoelectron spectroscopy (XPS) was used to analyze the chemical composition by observing the behaviour of the Ti2p, N1s and C1s lines. Binding energy analysis confirmed TiN and TiC formation. The C1s and Ti2p peaks shifted with increasing XPS sputtering time, thus revealing hydrocarbides contamination. Furthermore, depth profiles of the TiN/TiC bilayers showed that the films grown at a substrate temperature of 150º C had a thicker TiN layer than the samples grown at 50º C. Nitrogen had diffused into the TiC layer and carbon into the TiN layer in both films.